POWER, LIBERTY AND AUTHORITY IN A CONTRACTUAL SOCIETY - Anichebe, Obiora; Ezebuiro, Anthony Udoka; Ojimba, Anthony Chimankpam; Obiora, Remigius Mmadubugwu (JOURNAL OF ECONOMICS AND ALLIED RESEARCH, 2021)
The stability of a bank is said to be a function of its Capital adequacy which in turn influences its performance. Commercial Banks in Nigeria operate under different levels of capital adequacy. This study therefore sought to examine the effect of capital adequacy ratio on the performance of listed commercial banks in Nigeria proxied by return on capital employed from 2014-2019. Data for this study, collected from the sampled commercial banks annual financial reports for the period covered, were analysed using panel regression. The study found that capital adequacy ratio had significant and positive effect on return on capital employed of listed commercial banks in Nigeria. Based on this finding, the Central Bank of Nigeria is advised to increase the Capital Adequacy Ratio of commercial banks and ensure that they are complied with. This is expected to bring about improved performance of the banking sector.